LncRNA MIR4435-2HG inhibits the progression of osteoarthritis through miR-510-3p sponging - Liu, Yingli (Exp Ther Med, 2020)
Osteoarthritis (OA) is a disorder of diarthrodial joints that can have multiple causes. Long non-coding RNAs (lncRNAs) participate in multiple diseases, including OA. It has recently been reported that the lncRNA microRNA 4435-2HG (MIR4435-2HG) is downregulated in OA tissues; however, the biological role of MIR4435-2HG during OA progression remains unclear. In the present study, interleukin (IL)-1β was used to establish an in vitro model of OA. Protein expressions of matrix metallopeptidase (MMP) 1, MMP13, collagen II, interleukin (IL)-17A, p65, phosphorylated (p)-p65, IκB and p-IκB in CHON-001 cells were detected by western blotting. Gene expressions of IL-17A, MIR4435-2HG and miR-510-3p in tissues or CHON-001 cells were measured by reverse transcription-quantitative PCR and western blotting, respectively. Cell Counting Kit-8 assay and immunofluorescence staining were used to investigate cell proliferation, and cell apoptosis was detected by flow cytometry. The association between MIR4435-2HG, miR-510-3p and IL-17A was investigated using the dual luciferase report assay. MIR4435-2HG and miR-510-3p overexpression were transfected into CHON-001 cells. The results demonstrated that miR4435-2HG overexpression significantly increased proliferation and inhibited apoptosis of CHON-001 cells. In addition, miR-510-3p was identified as the downstream target of MIR4435-2HG, and miR-510-3p directly targeted IL-17A. The results from the present study suggested that MIR4435-2HG could mediate the progression of OA by inactivating the NF-κB signaling pathway. In addition, miR4435-2HG overexpression inhibited OA progression, suggesting that miR4435-2HG may be considered as a potential therapeutic target in OA.